Literature Review: Pengaruh Pantangan Makanan Karena Faktor Sosial Budaya Terhadap Kondisi Gizi Ibu Hamil - Dewi, Bekti Nirmala; Rahayu, Erni Dwi; Ariyanto, Khansa Salsabila Putri; Rahmadani, Rizki Tri; Rachmawati, Windi Chusniah (Prosiding Seminar Kesehatan Nasional Sexophone, 2024)
Every pregnant woman needs a balanced and complete nutritional intake for the health of the mother and fetus. However, a culture of dietary restrictions can limit the intake of important nutrients. This study aims to analyze the influence of cultural dietary restrictions on the nutritional status of pregnant women. This research uses a literature review method by analyzing various scientific sources, such as research journals, scientific articles and official reports. Based on literature analysis, it was found that the culture of food taboos has a significant influence on the nutritional status of pregnant women in Indonesia. Several types of food that are often taboo for pregnant women in Indonesia include fish, meat, eggs, pineapple and coffee. This taboo is based on various beliefs and myths that have no scientific basis. This belief can cause pregnant women to lack important nutrients, which can have fatal consequences for the health of the mother and fetus. Cultural dietary restrictions are one of the factors that can influence the nutritional status of pregnant women in Indonesia. Certain food restrictions can limit the intake of important nutrients for pregnant women, thereby increasing the risk of Chronic Energy Deficiency (CED), anemia, and various other pregnancy complications. Health workers can make several efforts, such as increasing knowledge through counseling and providing the public with the best possible understanding of the importance of consuming sufficient amounts of nutritious food, especially protein consumption, so that optimal nutritional status for pregnant women can be realized.